Prenatal diagnosis of MPPH syndrome. (24th January 2013) - De Keersmaecker, Bart; Van Esch, Hilde; Van Schoubroeck, Dominique; Claus, Filip; Moerman, Philippe; De Catte, Luc
ABSTRACT We report the prenatal sonographic detection of a fetus with megalencephaly, polymicrogyria, postaxial polydactyly and hydrocephaly. Only 14 patients have been reported in the literature so far, all but one were diagnosed postnatally. The polymicrogyria in the frontoparietal lobe was confirmed by prenatal magnetic resonance imaging. Additionally, a hypoplastic thymus as seen in a 22q11 deletion was present. Although polymicrogyria along with pre‐axial polydactyly has been described in 22q11 deletion, the diagnosis of Di George syndrome was ruled out. The etiology of megalencephaly, polymicrogyria, postaxial polydactyly and hydrocephaly has not been revealed yet. A dominant as well as recessive inheritance has been suggested. © 2013 John Wiley & Sons, Ltd.